The prevalence of hypogonadism in men with type 2 diabetes mellitus in clinical practice - Galina A. Melnichenko (Endocrinology Research Centre, 2019)
BACKGROUND: Hypogonadism is a common complication in men with type 2 diabetes mellitus (DM), but its prevalence remains unknown. AIMS: To estimate the prevalence of hypogonadism in men with type 2 DM. MATERIALS AND METHODS: Male patients with type 2 DM were enrolled into a single-cohort contemporaneous multicenter non-interventional screening study. The study period was from November 2017 through August 2018. Assessments included total testosterone, luteinizing hormone (LH), sex hormone-binding globulin, HbA1c levels. Levels of free testosterone were calculated by Vermeullen method. RESULTS: TheThe median of age of 400 included men was 56 years [51; 58], total testosterone was 12.3 [9.2; 16.5] nmol/l, free testosterone – 270 [217; 334] pmol/l, HbA1c – 7,1% [6.1; 8.6]. Hypogonadism was found in 135 men (33.7%). The total testosterone level in that group was 7.9 [6.8; 9.8] nmol/l, and free testosterone – 192 [164; 227] pmol/l. In hypogonadism-free men their levels were 15,1 [12,4; 18,6] nmol/l and 311 [270; 364] pmol/l, respectively. In most patients with hypogonadism LH level was low, but within normal ranges, and significantly lower than in men without hypogonadism – 3.2 [2.1; 4.7] IU/L vs 3.8 [2.7; 4.9] IU/L, respectively (p=0.007). Most commonly hypogonadism was with normal LH levels (92,6%, median LH level 3.2 [2.2; 4.3] IU/L, p<0,001). The frequency of hypogonadism with high LH level (10.2 [9.2; 14.7] IU/L) and low LH level (1.0 [0.6; 1.1] IU/L) was 4.4% and 3.0%, respectively. CONCLUSIONS: The prevalence of hypogonadism in men with type 2 DM was found to be 33.7%. Normal levels of LH are typical for this type of patients with hypogonadism.